2013
DOI: 10.1071/aj12098
|View full text |Cite
|
Sign up to set email alerts
|

An updated stratigraphic framework for the Georgina Basin, NT and Queensland

Abstract: The Georgina Basin is a Neoproterozoic to Lower Devonian sedimentary basin covering 325,000 km2 of western Queensland and the NT. It is a northwest-southeast-trending extensional basin, with prospective conventional and unconventional hydrocarbon targets in Cambrian and Ordovician carbonate and siliciclastic rock units. The unconventional gas and oil potential of the basin has led to recent exploration interest, although the basin has been relatively less explored in the past. At the southern end of the basin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Thickest sequences are preserved away from the McArthur Basin in the southern North Australian Craton, where Cambrian–Devonian rocks reach a maximum thickness of ca. 2.2 km (Smith et al, 2013), although many units observed in the southern Georgina Basin are absent in the McArthur Basin (Ahmad & Munson, 2013; Dunster et al, 2007). The McArthur and Georgina basins were subsequently unconformably overlain by the Jurassic–Cretaceous Carpentaria Basin (Abbott et al, 2001; Ahmad & Munson, 2013; Carson et al, 1999; Dunn, 1963; McConachie et al, 1990; Sweet et al, 1999), which thinly overlies much of the onshore North Australian Craton.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Thickest sequences are preserved away from the McArthur Basin in the southern North Australian Craton, where Cambrian–Devonian rocks reach a maximum thickness of ca. 2.2 km (Smith et al, 2013), although many units observed in the southern Georgina Basin are absent in the McArthur Basin (Ahmad & Munson, 2013; Dunster et al, 2007). The McArthur and Georgina basins were subsequently unconformably overlain by the Jurassic–Cretaceous Carpentaria Basin (Abbott et al, 2001; Ahmad & Munson, 2013; Carson et al, 1999; Dunn, 1963; McConachie et al, 1990; Sweet et al, 1999), which thinly overlies much of the onshore North Australian Craton.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…The basalts overlap more of the Grant Group in the Oobagooma and Willara Sub‐basins which may be due to localized subsidence throughout the Paleozoic and Mesozoic (Craig et al., 1984; Müller et al., 2005). Moreover, basalts above the Grant Group in the Canning Basin may be absent due to erosion as the top of the Grant Group is marked by a regional unconformity that persists into the Triassic (Kelman et al., 2013; Luck, 1991; Rollet et al., 2019; Smith et al., 2013; see Supplementary Material A in Yule & Spandler, 2021). Therefore, using these stratigraphic relationships and available geochronological data (Table 1; Gleadow & Duddy, 1984; Reeckmann & Mebberson, 1984), the basalt component is interpreted to have been emplaced with a 50 Myr time window in the Permo‐Triassic.…”
Section: Discussionmentioning
confidence: 99%
“…The Canning Basin is divided into onshore and offshore components (Figure 1). Near continuous deposition from Ordovician to present has produced thick, mostly Paleozoic stratigraphic packages, including the regionally extensive and up to 2,500 m thick Grant Group (Smith et al., 2013; Totterdell et al., 2014; Yeates et al., 1984). These packages contain a variety of sedimentary rocks including limestone, sandstone, mudstone and siltstone.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…The predominant units of the Georgina Basin are Cambrian to Ordovician platformal successions (limestone and dolomite, with phosphorite, chert, siltstone and shale units) with minor Neoproterozoic to earliest Paleozoic siliciclastic and fluvioglacial successions in the deeper parts of the basin to the south (the Toko and Dulcie Synclines as well as the Burke River Structural Belt; Figure 1). Sparse outcrops of Devonian sandstone cap the Cambrian platformal successions (Smith et al., 2013). The Cambrian succession is of greatest economic importance due to its association with the main phosphate deposition event (Cook, 1972; Southgate, 1986) and significant hydrocarbon potential (Ambrose et al., 2001; Lodwick & Lindsay, 1990).…”
Section: Geological Settingmentioning
confidence: 99%